Nutritional supplements and mother's milk composition: a systematic review of interventional studies - Mojtaba Keikha; Ramin Shayan-Moghadam; Maryam Bahreynian; Roya Kelishadi (BMC, 2021)
Abstract Background This study aims to systematically review the effects of maternal vitamin and/or mineral supplementation on the content of breast milk. Methods We systematically searched electronic databases including Medline via PubMed, Scopus and ISI Web of Science till May 24, 2018. The following terms were used systematically in all mentioned databases: ("human milk" OR "breast milk" OR "breast milk composition" OR "human breast milk composition" OR "composition breast milk" OR "mother milk" OR "human breast milk" OR "maternal milk") AND ("vitamin a" OR "retinol" OR "retinal" OR "retinoic acid" OR "beta-carotene" OR "beta carotene" OR "ascorbic acid" OR "l-ascorbic acid" OR "l ascorbic acid" OR "vitamin c" OR "vitamin d" OR "cholecalciferol" OR "ergocalciferol" OR "calciferol" OR "vitamin e" OR "tocopherol" OR "tocotrienol" OR "alpha-tocopherol" OR "alpha tocopherol" OR "α-tocopherol" OR "α tocopherol" OR "vitamin k" OR "vitamin b" OR "vitamin b complex" OR "zinc" OR "iron" OR "copper" Or "selenium" OR "manganese" OR "magnesium") and we searched Medline via Medical subject Headings (MeSH) terms. We searched Google Scholar for to increase the sensitivity of our search. The search was conducted on human studies, but it was not limited to the title and abstract. Methodological quality and risk of bias of included studies were evaluated by Jadad scale and Cochrane risk of bias tools, respectively. Results This review included papers on three minerals (zinc, iron, selenium) and 6 vitamins (vitamin A, B, D, C, E and K) in addition to multi-vitamin supplements. Although studies had different designs, e.g. not using random allocation and/or blinding, our findings suggest that maternal use of some dietary supplements, including vitamin A, D, vitamin B1, B2 and vitamin C might be reflected in human milk. Vitamin supplements had agreater effect on breast milk composition compared to minerals. Higher doses of supplements showed higher effects and they were reflected more in colostrum than in the mature milk. Conclusion Maternal dietary vitamin and/or mineral supplementation, particularly fat- soluble vitamins, vitamin B1, B2 and C might be reflected in the breast milk composition. No difference was found between mega dose and single dose administration of minerals.